SOĞUK SAVAŞ'IN BİTİŞİNDEN ADANA MUTABAKATI'NA: TÜRKİYE-SURİYE İLİŞKİLERİNDE FIRAT NEHRİ SORUNU (1990-1998) - Yildirim, Zafer (TURAN : stratejik arastirmalar merkezi, 2025)
This study examines the Euphrates River issue in Turkey-Syria relations during the post-Cold War period (1990-1998). The dispute, which formed the basis of the problem, deepened with Turkey's Southeastern Anatolia Project (GAP) initiative and its view of the Euphrates as "transboundary waters," while Syria considered the Euphrates "international waters" and demanded equitable sharing. Syria's increasing water insecurity and Turkey's linking of the water issue to the support given to the PKK terrorist organization escalated tensions. Failed negotiations and conflicting legal positions left the problem unresolved. The 1998 Adana Agreement, achieved through Turkish military pressure, ensured Syria's cessation of support for the PKK but did not resolve the fundamental Euphrates water dispute, carrying it into the future. The study aims to reveal how the water-security nexus and power asymmetry